Perbandingan Proprioceptive Neuromuscular Facilitation (PNF) dan Fleksibilitas Statis Terhadap Pemulihan Pemain Sepak Bola Boya FC Makassar - Darul Husnul (Gerak: Journal of Physical Education, Sports, and Health, 2022)
This study aims to see the recovery process using the PNF (Proprioceptive Neuromescular Facilition) method using a type of experimental research with a total sample of 20 BOYA football players. FC Makassar. The research design used is Pre Test – Post Test Group Design.the results of the study show that the analysis of X1 and X2 data obtained a sig value of 0.00 (sig < 0.05), with a difference of 2.40, and the results of data analysis X3 and X4 obtained a sig value of 0.00 (sig < 0.05), with a difference of 1.92 means that there is an effect of the recovery process by looking at the lactate azam between the stretching process with PNF and static recovery. While the difference between PNF and Static Flexibility is 0.47 with a sig value. 0.00 (Sig < 0.05), which means that stretching with the PNF method is better compared to static stretching.